PERBANDINGAN HASIL TANAMAN PAKCHOY (Brassica rapa) DENGAN PEMBERIAN PUPUK ORGANIK YANG BERBEDA - Sirlyana Sirlyana; Surtinah Surtinah (Universitas Lancang Kuning, 2019)
The purpose of this study was to obtain an alternative substitute for manure in the cultivation of Pakchoy plants. The experimental study was conducted using two treatments, namely manure and compost of sweet corn plants, the treatment was repeated 10 times, the statistical test used was the unpaired t-test. To achieve the objectives of the study, observations were made on the growth and yield of Pakchoy. The recommended research results are that sweet corn compost can be used as a substitute for manure in Pakchoy's culture